The re-greening of east coast Australian rivers: An unprecedented riparian transformation - Cohen, Tim J.; Suesse, Thomas; Reinfelds, Ivars; Zhang, Nuosha; Fryirs, Kirstie; Chisholm, Laurie (The Science of the total environment, 2022)
Eastern Australia has a climate characterised by extreme variability and the occurrence of multiple years of drought conditions. Arguably one of the severest droughts on record – the Big Dry ended in many areas with the La Niña of 2009/2010. A succession of subsequent dry years brought a return to drought conditions across much of eastern Australia in 2018 and 2019, ending with the catastrophic fires of 2019/2020. An analysis of river gauges in eastern Australia demonstrates that unregulated rivers have been subject to reduced monthly and total annual flow for far longer than the recent multi-year droughts. A breakpoint regression model on the annual streamflow data shows statistically significant declines in total annual flow (by up to a factor of three) since 1992/93 on the far South coast of New South Wales (NSW). In the monthly data, fifteen of the nineteen gauges analysed exhibit modelled breakpoints, but with statistically significant differences in monthly mean discharge between consecutive periods only occurring in three of these gauges (occurring between 1972 and 1993 in both the North and South coast). The trend toward reduced flow over the last few decades has, for many rivers, coincided with land use and river management changes resulting in increases in woody riparian vegetation. To show this we use a remote sensing technique and estimate the magnitude of vegetation change along all major rivers and their tributaries on the eastern seaboard of NSW (28 catchments with total river length assessed of 19,750 km) using a normalized difference vegetation index (NDVI) analysis of woody vs non-woody riparian vegetation extent. Predicted vegetation change between 1987 and 2020 is spatially variable across catchments but the mean increase in woody riparian vegetation across all catchments is 9–51% (0.2 and 0.1 NDVI increases). Such increases are perhaps the largest biogeomorphic change the SE Australian drainage network has experienced since the initial clearance of vegetation associated with European colonisation in the late 18th and early 19th centuries. [Display omitted] •Climate change could impact annual streamflow.•Unregulated rivers in eastern Australia have declined in streamflow since 1990.•The decline in streamflow has coincided with regrowth of riparian woody vegetation.•Remote sensing of 19,750 km of river shows a 9–51% increase since 1987.•Riparian vegetation increase coincides with changes in river management and landuse.